Exploring cross-modal plasticity in the auditory–visual cortex post cochlear implantation: implications for auditory and speech function recovery and mechanisms - Qiao, Xiao-Feng; Liu, Lu-Dan; Han, Ling-Yan; Chen, Ying; Li, Xin (Frontiers in Neuroscience, 2024)
Objective The aim of this is to explore changes in cross-modal reorganization within the auditory–visual cortex after cochlear implantation, examining their influence on auditory and speech functions along with their underlying mechanisms. Methods Twenty prelingually deaf children who received cochlear implantation and rehabilitation training at our hospital between February 2022 and February 2023 comprised the prelingual deaf group. Simultaneously, 20 healthy children served as the control group. The prelingual deaf group underwent brain cortical activity assessment and evaluation of auditory-speech recovery pre-surgery, at postoperative weeks 1 and 2, and at months 1, 3, 6, 9, and 12. The control group underwent parallel assessments and evaluations. We analyzed the correlation between cortical activity in the auditory–visual cortex of patients and their auditory-speech functional recovery. Results The group with prelingual deafness displayed elevated levels of auditory and visual cortical electromagnetic intensity compared to the control group, both prior to and 9 months after surgery. However, by the 12-month mark post-surgery, there was no discernible distinction between the two groups. Following surgery, the prelingually deaf group exhibited a progressive improvement in both Categories of Auditory Performance (CAP) and Speech Intelligibility Rate (SIR), initially lagging behind the control group. Notably, a negative correlation emerged between auditory and visual cortical electromagnetic intensity values and CAP/SIR scores at the 12-month post-surgery assessment. Conclusion Cochlear implantation in prelingually deaf children results in elevated activity within the auditory and visual cortices, demonstrated by heightened electromagnetic intensity readings. Cross-modal reorganization is observed temporarily at 3 months post-surgery, which resolves to baseline levels by 12 months post-surgery. This phenomenon of reversal correlates with the restoration of auditory and speech functions in these children.